Bringing the Clinic into the 21st Century - Julie Macfarlane (The Windsor Yearbook of Access to Justice, 2009)
Emerging in the 1960’s, the clinical legal education movement promoted an important dual mission – the training of law students in practical client advocacy and the service of under and un-served communities. These laudable goals spawned a movement of great significance for legal education. At its peak the clinical movement can point to hundreds of clinics in law schools across the world, specially appointed clinical faculty, a law review and the development of a voluminous literature on clinical teaching methodology. However in the last 10 years student interest, funding and scholarly attention to the legal clinics has faded. This article argues that this is in part due to the mission and ideology of the law school clinics remaining “stuck” in a conception of social justice lawyering that is heavily dependent on rights-based strategies and traditional, hierarchical conceptions of the lawyer/client relationship. While reflecting the same stasis that affects the wider law school curriculum, this disconnect from the needs of contemporary clients as well as an increasingly pluralist model of legal services has unique implications for the legal clinics.